Uptake of voluntary medical male circumcision among men with sexually transmitted infections in Lilongwe, Malawi: a protocol for a pre-interventional and post-interventional study - Mina C Hosseinipour; Mitch M Matoga; Sara Jewett; Charles Chasela (BMJ Open)
Introduction Voluntary medical male circumcision (VMMC) is one of the key interventions for HIV prevention. However, its uptake among men in Malawi is low. Implementation science strategies for demand creation of VMMC increase uptake. We designed an implementation science demand-creation intervention to increase the uptake of VMMC among men with sexually transmitted infections (STIs).Methods and analysis We designed a pragmatic pre-interventional and post-interventional quasi-experimental study combined with a prospective observational design to determine the uptake, acceptability, appropriateness and feasibility of a multifaceted intervention for scale up of uptake of VMMC among men with STIs at Bwaila STI clinic in Lilongwe, Malawi. The intervention includes transport reimbursement (R), intensified health education (I) and short messaging service (SMS)/telephonic tracing (Te) (RITe). The intervention will be implemented in phases: pre-implementation and implementation. Pre-implementation phase will be used for collecting baseline data, while the RITe intervention will be rolled-out in the implementation phase. The RITe intervention will be implemented in a sequential and incremental manner called implementation blocks: block 1: intensified health education; block 2: intensified health education and SMS/telephonic tracing; and block 3: intensified health education, SMS/telephonic tracing and transport reimbursement. The target sample size is 80 uncircumcised men for each intervention block, including the pre-implementation sample, making a total of 320 men (280 total, 70 per block will be surveyed). The primary outcome is uptake of VMMC during the implementation period. Mixed methods assessments will be conducted to evaluate the acceptability, appropriateness and feasibility of the RITe intervention.Ethics and dissemination The study protocol was approved by the Malawi’s National Health Sciences Research Ethics Committee (approval number: 19/10/2412), University of North Carolina at Chapel Hill’s Institutional Review Board (approval number: 19–2559) and University of the Witwatersrand’s Health Research Ethics Committee (approval number: M200328). Results will be disseminated via publication in a peer-reviewed journal and presentations at relevant scientific conferences and meetings.Trial registration number NCT04677374.